Question and Answers Forum

All Questions      Topic List

Trigonometry Questions

Previous in All Question      Next in All Question      

Previous in Trigonometry      Next in Trigonometry      

Question Number 118078 by bemath last updated on 15/Oct/20

3(cos x+sin x)^4 +6(sin x−cos x)^2 −  3(sin^6 x+cos^6 x) = ?

3(cosx+sinx)4+6(sinxcosx)23(sin6x+cos6x)=?

Answered by bobhans last updated on 15/Oct/20

(1) (sin x+cos x)^4 =(1+sin 2x)^2                                             =1+2sin 2x+sin^2 2x  (2)(sin x−cos x)^2 =1−sin 2x  (3)sin^6 x+cos^6 x = (sin^2 x)^3 +(cos^2 x)^3         = 1(sin^4 x−sin^2 xcos^2 x+cos^4 x)        =(sin^2 x)^2 +(cos^2 x)^2 −(1/4)sin^2 2x         = 1−2sin^2 xcos^2 x−(1/4)sin^2 2x         = 1−(3/4)sin^2 2x  Now we want compute 3×(1)+6×(2)−3×(3)  ⇒3+6sin 2x+3sin^2 2x+6−6sin 2x−  (3−(9/4)sin^2 2x) = 9+3sin^2 2x−3+(9/4)sin^2 2x  = 6+((21)/4)sin^2 2x

(1)(sinx+cosx)4=(1+sin2x)2=1+2sin2x+sin22x(2)(sinxcosx)2=1sin2x(3)sin6x+cos6x=(sin2x)3+(cos2x)3=1(sin4xsin2xcos2x+cos4x)=(sin2x)2+(cos2x)214sin22x=12sin2xcos2x14sin22x=134sin22xNowwewantcompute3×(1)+6×(2)3×(3)3+6sin2x+3sin22x+66sin2x(394sin22x)=9+3sin22x3+94sin22x=6+214sin22x

Answered by MJS_new last updated on 15/Oct/20

3(c+s)^4 +6(s−c)^2 −3(s^6 +c^6 )=  =−3(c^6 +s^6 −c^4 −s^4 −4c^3 s−4cs^3 −6c^2 s^2 −2c^2 −2s^2 +4cs)=       [c=(√(1−s^2 ))]  =−3(7(s^4 −s^2 )−2)=  =3(7s^2 (1−s^2 )+2)=  =3(7s^2 c^2 +2)=  =6+21sin^2  x cos^2  x =  =6+((21)/4)sin^2  2x =  =((69)/8)−((21)/8)cos 4x

3(c+s)4+6(sc)23(s6+c6)==3(c6+s6c4s44c3s4cs36c2s22c22s2+4cs)=[c=1s2]=3(7(s4s2)2)==3(7s2(1s2)+2)==3(7s2c2+2)==6+21sin2xcos2x==6+214sin22x==698218cos4x

Commented by bemath last updated on 15/Oct/20

short cut way

shortcutway

Terms of Service

Privacy Policy

Contact: info@tinkutara.com